Academic Supervision Using the Plan, Do, Check, And Action (PDCA) Method from William Edwards Deming's Perspective to Improve Teacher Professionalism in Public Junior High Schools in Kabupaten Anambas - Nurhasanah, Nurhasanah; Asrulla, Asrulla; Afriza, Afriza; Agustiar, Agustiar (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the implementation of the PDCA cycle (Plan, Do, Check, Act) in academic supervision and its impact on teacher professionalism in public junior high schools (SMP) in Kabupaten Anambas. The study is motivated by the need to enhance teacher professionalism, which includes lesson planning, assessment, reflection, and professional collaboration. Academic supervision has so far tended to be administrative in nature, making the application of the PDCA cycle—introduced by William Edwards Deming—relevant for creating supervision that is systematic, reflective, and oriented toward continuous improvement. This study uses a qualitative approach with a case study method conducted in three public junior high schools (SMPN 1 Siantan Utara and SMPN 2 Bayat). Data were collected through in-depth interviews with teachers, principals, and supervisors; observations of supervision documents and lesson plans (RPP); and focus group discussions. Thematic analysis was used to identify changes in practice and contextual factors influencing the implementation of PDCA. The results show that PDCA-based academic supervision improves more thorough lesson planning, more consistent professional reflection, concrete follow-up actions, and more intensive teacher collaboration. However, the success of PDCA implementation is influenced by enabling factors such as transformational school leadership, supervisor support, teacher openness, availability of supervision instruments, and an organizational culture that supports learning; and it is hindered by time constraints, varying levels of understanding of PDCA, administrative workload, resistance from entrenched cultural norms, and limited technology. These findings reinforce the theory that PDCA-based academic supervision is more effective than conventional models and provide practical recommendations for policies aimed at improving the quality of education in public junior high schools.